IFPA meeting 2014 workshop report: Animal models to study pregnancy pathologies; new approaches to study human placental exposure to xenobiotics; biomarkers of pregnancy pathologies; placental genetics and epigenetics; the placenta and stillbirth and fetal growth restriction. (April 2015) - Barbaux, S.; Erwich, J.J.H.M.; Favaron, P.O.; Gil, S.; Gallot, D.; Golos, T.G.; Gonzalez-Bulnes, A.; Guibourdenche, J.; Heazell, A.E.P.; Jansson, T.; Laprévote, O.; Lewis, R.M.; et al.
Abstract: Workshops are an important part of the IFPA annual meeting as they allow for discussion of specialized topics. At IFPA meeting 2014 there were six themed workshops, five of which are summarized in this report. These workshops related to various aspects of placental biology but collectively covered areas of animal models, xenobiotics, pathological biomarkers, genetics and epigenetics, and stillbirth and fetal growth restriction.